The Role of Teacher Characteristics and Managerial Support in Implementation of History and Government Curriculum in Wareng District, Kenya - Ruto, Zipporah Jerotich (International Journal of Management and Sustainability, 2013)
This paper undertakes an assessment of the extent of professional support that the teachers of History and Government subject are accorded by the schools’ management. The study investigated the challenges of teaching History and Government in Kenyan secondary schools as experienced by teachers in Wareng District, located in the North Rift region of Kenya. The study adopted a descriptive survey design. Simple and stratified random sampling techniques were used to select a sample of 120 respondents from the History and Government teachers of the secondary schools in the study area. Questionnaires, interview and observation schedules were used to collect data. Data was analyzed using descriptive statistics. These comprised frequencies and percentages. Data collected was presented using tables. The study revealed that there was inadequate support in the acquisition and purchasing of instructional materials for teaching the subject, teacher recruitment issues, provision of funds for seminars and workshops, and rewarding of high performing teachers. Most teachers also reported underestimation of the importance of History and Government subject by the head teachers of their school. The study recommends the need for professional managerial support to the teaching of history and government in secondary schools. The findings of this study are intended to benefit the school management, teaching staff, educational planners and other stake-holders in identifying the challenges faced by teachers and adopting concerted efforts to overcome them.